A LINGUISTIC LANDSCAPE OF VALUES ON SANJAI SHOP SIGNS IN BUKITTINGGI AND AGAM: LANSKAP LINGUISTIK NILAI-NILAI PADA TANDA TOKO SANJAI DI BUKITTINGGI DAN AGAM - Tia Kharina Elvonny; Nadra Nadra (Jurnal Kata, 2022)
Sanjai is one of the typical foods in Bukittinggi. Sanjai is a type of cracker made from cassava which is thinly grated and then fried. Sanjai shops are very easy to find, ranging from small shops to large shops. One of the unique aspects of the Sanjai store is the values ​​contained in the names, labels, and symbols found on the shops’ sign. The expression of values ​​in names, labels and symbols is called the linguistic landscape of values. This research is an attempt to examine the value on the signboard of the Sanjai shop. The data of this research are the names, labels and symbols on the signboards of Sanjai shops in Bukittinggi and Agam. The research was conducted qualitatively. The data are collected by using observational method with recording and note taking techniques. Data analysis was carried out from the perspective of the linguistic landscape, namely the approach used to examine the landscape of language in public spaces. The data analysis of the research applied the referentional and pragmatic identity method (Sudaryanto, 2015). These analytical methods are used to identify and explore the values ​​contained in the names, labels and symbols on the Sanjai shop sign. Based on the results of data analysis, six values ​​were found, namely: economic value, identity value, religious value, power value, solidarity value and artistic value.